Analysis of Mathematical Communication Skills of Grade VIII Students in Solving Statistical Problems Based on Learning Style - Ferdianto, Ferry; Oktaviani, Anisa (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
Mathematical communication skills are very important for students' success in understanding and solving mathematical problems. However, this ability can be affected by a variety of factors, including the student's learning style. This study aims to analyze the mathematical communication skills of grade VIII students in solving statistical problems based on students' learning styles. This study uses a qualitative descriptive method, with 36 students and three students from Class VIII D at SMPN 7 Cirebon City, each representing a different dominant learning style: visual, auditory, and kinesthetic. Data were collected through learning style questionnaires, written tests, observations, interviews, and documentation. The results of the study revealed that students with visual learning styles met all indicators, students with auditory learning styles met three out of four indicators, while students with kinesthetic learning styles only met two indicators. These findings suggest that students' mathematical communication abilities vary depending on their learning style, with visual and auditory learners showing stronger mathematical communication abilities compared to kinesthetic learners. The implications of these results emphasize the need for different teaching strategies to accommodate different learning styles in mathematics learning. By addressing these differences, educators can further support the development of mathematical communication skills across different learning styles of students, ultimately improving academic performance and overall mathematical comprehension.